A Simple and Direct Preparation of a Substrate‐Free Interconnected Nanostructured Carbon Electrode from Date Palm Leaflets for Detecting Hydroquinone. Issue 17 (14th June 2017) - Aziz, Md. Abdul; Theleritis, Demetrios; Al‐Shehri, Mohammod Oudah; Ahmed, Muhammad Ibrar; Qamaruddin, Muhammad; Hakeem, Abbas Saeed; Helal, Aasif; Qasem, Mohammed Ameen Ahmed
Abstract: Preparation of carbon nanomaterials from agro‐waste is a promising research area due to the low cost and high availability of agro‐waste and the unique physical, chemical and electrochemical properties of agro‐waste‐derived carbon. Such prepared nanomaterials have been used as electrode materials after immobilizing them on other solid substrates such as glassy carbon, Au, and Pt electrodes. However, this immobilizing step is tedious and the substrate electrodes are expensive. Here we present a simple pyrolytic preparation of a substrate‐free electrode consisting of interconnected nanostructured carbon from date palm leaflets for direct use as an inexpensive electrode material. The prepared nanostructure was characterized using field emission scanning electron microscopy, energy dispersive spectroscopy, X‐ray photoelectron spectroscopy, Raman spectroscopy, and cyclic voltammetry. The cyclic voltammetry studies revealed the electrocatalytic properties of the prepared nanostructured electrode toward K4 [Fe4 (CN)6 ] and hydroquinone (HQ) to be superior to those of the commonly employed glassy carbon electrode. The prepared nanostructured carbon electrode was deployed using amperometry to sensitively detect HQ, and showed a detection limit for HQ of 6.1 μM. This electrode was highly stable and selective for HQ in the presence of several test interferents. The developed electrode may thus be considered as a promising tool for sensing HQ. Abstract : Cyclic voltammogram of 5 mM K4 [Fe(CN)6 in 0.1 M KCl (aq.) at a substrate‐free interconnected nanostructured carbon electrode prepared from date palm leaflets